TANGGUNG JAWAB OTORITAS JASA KEUANGAN DALAM PENANGGULANGAN PENIPUAN INVESTASI - Heru Suyanto; Andriyanto Adhi Nugroho; Surahmad Surahmad (Prodi Hukum S1 - Fakultas Hukum - Universitas Pamulang, 2018)
Abstract The Financial Services Authority (OJK) is an institution that has the functions, duties and authority to regulate, supervise, examine and investigate. In addition OJK also has the duty and authority to protect consumers throughout the financial services sector. In the task of protecting consumers regulated in article 28 of Law No. 21 of 2011, includes providing information and education to the public on the characteristics of the financial services sector, services and products; ask the Financial Services Institution to stop its activities if the activity has the potential to harm the community; and other actions deemed necessary in accordance with the provisions of legislation in the financial services sector